Erin Pittman: capstone - Pittman, Erin, artist (Colorado State University. Libraries, 2017)
The artist's statement: I have always attempted to express myself as an ever-changing and evolving human and artist in my artwork by exploring various life experiences, emotions, and growth. Self-reflection and development is something I work on quite a bit and love to express in my artwork. As a transparent person with my heart on sleeve, I found that creating artistic expressions helps to release some of the emotions I've experienced in life. There are waves in my work that vary from dark and moody to light and colorful, depending on what's going on at the time. Recently, my designs have become very simple and type based, inspired by my interest in street art and calligraphy. Much of what has inspired me has come from my experiences with travel - learning about other cultures and seeing their art has become very important to me. Some of my favorite works of art are those that are not spoken of, like murals on the wall in a third world country or an unsigned painting in someone's home. More importantly, I am influenced by the people I meet and their stories, and I strive to continue to find influence in that to add to my art.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design